METODE MENULIS BERANTAI UNTUK MENINGKATKAN MOTIVASI DAN KETERAMPILAN MENULIS PANTUN SISWA - Sella Permata Sari; Sumarwati Sumarwati; Atikah Anindyarini (Universitas Sebelas Maret, 2020)
In writing pantun ‘Indonesian rhymes’ there are certain rules which become a source of difficulty for students, such as taxation, syllable numbers, number of words, number of sentences, so that not all students are interested and motivated to do the pantun writing task. For this reason, learning should be fun and motivating each other through chain writing. This research is a classroom action research to improve motivation and writing skills of students in class VIIA SMP Negeri 1 Kebakkramat. The research action was carried out in two cycles. To analyze the data used comparative descriptive statistical analysis techniques and critical analysis. The results showed that the application of the chain writing method increased motivation and pantun writing skills. This improvement can be done with the following learning procedures: (1) the class is divided into 8 groups, each consisting of 4 students; (2) students and teachers determine the theme of pantun; (3) students and group members make pantun, (4) students make the first row of pantun; (5) the second student makes one next line and the next line is continued by other students in the group until a complete pantun is formed; (6) at the end of each line students write the initials to mark the name of the author; (7) students and their groups make revisions; (8) rhymes are then read in turn by group members; and (9) teachers and other groups assess the pantun read.